Divorce Outside the Religious Courts in the Citereup Bogor Community - Septiani, Rina; Maulidini, Putri; Taufiq, Arif (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2023)
The divorce regulations that apply in Indonesia are stated in article 39 of the 1974 Law (1). Divorce only can done in front hearing Court after the relevant Court tried and was unsuccessful reconcile second both parties. (2). For do divorce must Enough reason that between husband the wife will not live in harmony as husband and wife. (3). System method divorce in front hearing Court in set in Â Â regulation separate legislation. However, this regulation does not apply to the entire community of Citereup which still adheres to Islamic Sharia law where divorce pronounced by a husband to a wife wherever the law is valid falls under divorce. The research method used is qualitative research based on field research which is oriented towards interviews, observation and documentation in order to obtain clear and accurate data. The results of the research are that the public's perception regarding divorce carried out outside the Religious Courts is that it is legal, the causal factors are: Lack of legal awareness in the community, costs are considered too burdensome for the parties to divorce, divorce procedures in the Religious Courts are considered complicated by the community. The impacts felt by society include: Divorce that has no legal force, difficulty in officially remarrying, unequal distribution of responsibilities.